2019
DOI: 10.3390/ijms20020308
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota Protects against MCD Diet-Induced Steatohepatitis

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in western countries, with a continuously rising incidence. Gut-liver communication and microbiota composition have been identified as critical drivers of the NAFLD progression. Hence, it has been shown that microbiota depletion can ameliorate high-fat diet or western-diet induced experimental Non-alcoholic steatohepatitis (NASH). However, its functional implications in the methionine-choline dietary model, remain incompletely understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 61 publications
4
38
0
1
Order By: Relevance
“…It is likely that the toxicities and weight loss associated with dietary L-Met restriction result from its effect on the gastrointestinal tract. In earlier studies, maintenance of animals on L-Met-and L-Met/choline-deficient diets, which cause nonalcoholic steatohepatitis, was reported to result in intestinal barrier deterioration, macroscopic shortening of the intestine and intestinal villi, and in gut microbial dysbiosis (57,58). Hepatocellular injury, oxidative stress, and high ALT levels are caused by a significant decrease in liver SAM and GSH in these models (59), which is not surprising given that >75% of the blood supplied to the liver is via the portal vein that collects blood from nearly the entire gastrointestinal tract (60).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the toxicities and weight loss associated with dietary L-Met restriction result from its effect on the gastrointestinal tract. In earlier studies, maintenance of animals on L-Met-and L-Met/choline-deficient diets, which cause nonalcoholic steatohepatitis, was reported to result in intestinal barrier deterioration, macroscopic shortening of the intestine and intestinal villi, and in gut microbial dysbiosis (57,58). Hepatocellular injury, oxidative stress, and high ALT levels are caused by a significant decrease in liver SAM and GSH in these models (59), which is not surprising given that >75% of the blood supplied to the liver is via the portal vein that collects blood from nearly the entire gastrointestinal tract (60).…”
Section: Discussionmentioning
confidence: 99%
“…Another finding of our study is that TMAO restored the diversity of gut commensal bacteria in rats fed a HFHC diet. Gut dysbiosis is a hallmark of NAFLD and NASH, in which reduced diversity of gut bacteria is an important characteristic[25,30]. Gut dysbiosis leads to gut bacteria translocation due to the impaired intestinal barrier and increased production of harmful microbial metabolites such as lipopolysaccharide and endogenous ethanol, which contribute to the pathogenesis and progression of NAFLD and NASH[31].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, due to the importance of choline as an essential nutrient, choline-deficient diets may also induce gut microbiota alterations and health problems [ 62 , 63 , 64 , 65 ]. Indeed, a human trial in which the choline intake was controlled demonstrated that the gut microbiota composition changed with dietary choline levels and specific alterations in Gammaproteobacteria , and Erysipelotrichi members were associated with changes in liver fat during choline depletion [ 66 ].…”
Section: Diet Impact On Microbiota-choline Metabolismmentioning
confidence: 99%
“…Choline-deficient diets have also been associated with NASH and may result in obesity and hyperglycemia [ 64 , 65 , 66 , 108 ]. Research indicates the role of choline-deficient diets in intestinal dysbiosis by reducing the microbiota diversity and altering the microbial population representation within the microbiome [ 64 , 65 , 109 ]. Subsequent transplantation of the microbiome of NASH individuals is sufficient in inducing NASH in otherwise healthy individuals [ 65 , 110 ].…”
Section: Choline Intake and Its Relationship To Diseasementioning
confidence: 99%